(untitled) (Journal of Sustainability, Environment and Peace, 2022)
Urban areas have been experiencing unprecedented growth since the beginning of the 20th century. Rapid urbanization is likely to present various challenges relating to human health, food security, water and energy needs, aesthetic and recreational spaces. Thus, the United Nations Agenda 2030 premised on economic, social and environmental sustainability may not be realized. This paper focuses on the recreational facilities in Karura Forest located in the peri-urban area of Nairobi City. It uses both quantitative and qualitative research design. In-depth literature review was used to enrich research findings. Data was collected from a selected sample of 1150 Nairobi residents. It provides an inventory of recreational facilities and examines the contribution open and green spaces make to the residents. The preferences of these residents to visit the facilities are also documented. The study found out that about 77.6% of the visitors came from nearby high-income areas of Muthaiga, Nyari, Rosslyn, Peponi and Runda, about 21.4% came from middle-income areas of Parklands, Mlolongo, Athi River and Langata while only a paltry 1% came from the low-income areas of Kangemi, Ngara, Huruma and DeepSea slums. Most of the visitors were between 14 and 52 years of age. Findings are expected to inform policy and future urban planning for green spaces and their recreational value. To ensure sustainable development in the future, there is need to preserve the existing open and recreational green facilities in Nairobi. Both the County and National Governments should formulate and implement the Sustainable Kenyan Cities Policy to preserve open and green spaces in the rapidly growing urban areas of the country.